Modernity as Disruption to Nature, People, and Culture in Things Fall Apart, Burung Kayu, and Isinga: Modernisasi sebagai disrupsi terhadap alam, manusia, dan budaya dalam Things Fall Apart, Burung Kayu, dan Isinga - Suryani, Rosalia; Dewi, Novita (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
Environmental degradation has become an important issue in the 21st century. Environmental destruction has never been free from exploitation, oppression, and marginalization. Through Indonesian and African novels Burung Kayu, Isinga, and Things Fall Apart, this paper attempts to reveal two research questions; first, how people, nature, and culture are interconnected with each other in the three novels, and second, how modernity becomes a disruption to the Mentawai, Aitubu, and Igbo. By comparing and contrasting the three novels, this paper uses library research. The research questions will be revealed through descriptive qualitative data. The approach used to analyze is postcolonial ecocriticism. The findings of the research are two. First, there is a connectedness of nature and people of the three communities manifested in ritual tradition, livelihood, social systems and values, and land ownership system. Second, the power dominance of the First World toward the Third World through modernity results in environmental destruction and cultural disruptions of the Mentawai, Aitubu, and Igbo indigenous. Humans are inseparable from living with other communities and over time, they will experience modernity. However, not all forms of modernity fit for a community. Therefore, they have two choices regarding modernity: to reject or accept it.